2003
DOI: 10.1021/ja027900v
|View full text |Cite
|
Sign up to set email alerts
|

Protonation of the Pyrimidine Ring at the C(5) Position:  Formation of a Stable Cationic σ-Complex

Abstract: NMR studies showed that, in addition to the expected N(1) protonation, 2,4,6-pyrimidinetriamine, N,N,N',N',N",N"-hexamethyl- (1) could also be protonated at the C(5) position in water, leading to an equilibrium between the C(5) and N(1) protonated forms. Analysis of the NMR titration data gives 6.87 and 6.89 for the pK(a) of the C(5) and N(1) protonation equilibria. Moreover, the reaction of 1 with chloroacetyl chloride leads to a novel 1,1-bis(pyrimidin-5-yl)-2-chloroethene type derivative (4) that is, peculi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 23 publications
1
20
0
Order By: Relevance
“…Elemental analysis and MS experiments showed that the anion is chlorine (1). We could rationalize the chemical formation of compound 16 and explained the observed carbon protonation by means of geometrical and electronic factors (1).…”
Section: Epiloguementioning
confidence: 96%
See 4 more Smart Citations
“…Elemental analysis and MS experiments showed that the anion is chlorine (1). We could rationalize the chemical formation of compound 16 and explained the observed carbon protonation by means of geometrical and electronic factors (1).…”
Section: Epiloguementioning
confidence: 96%
“…Therefore, by excluding accidental isochrony, the rotation of these dimethylamino groups should be fast in unit A and slow in unit B on the NMR chemical shift timescale. Based on the foregoing symmetry considerations, the 12H-intensity minor and major 1 H methyl signals at ␦ 2.78 and ␦ 2.79 can be assigned to the Me 2 N(4,6) …”
Section: Stagementioning
confidence: 99%
See 3 more Smart Citations